2018
DOI: 10.1093/aje/kwy095
|View full text |Cite
|
Sign up to set email alerts
|

Medical History, Medication Use, and Risk of Nasopharyngeal Carcinoma

Abstract: Because persistent inflammation may render the nasopharyngeal mucosa susceptible to carcinogenesis, chronic ear-nose-throat (ENT) disease and its treatment might influence the risk of nasopharyngeal carcinoma (NPC). Existing evidence is, however, inconclusive and often based on methodologically suboptimal epidemiologic studies. In a population-based case-control study in southern China, we enrolled 2,532 persons with NPC and 2,597 controls, aged 20-74 years, from 2010 to 2014. Odds ratios were estimated for as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 34 publications
1
22
0
Order By: Relevance
“…Because of the overall lack of association with NPC risk, our findings suggest that anti‐inflammatory treatment with herbal tea is unlikely to play a causal role in NPC prevention. This result is consistent with our prior finding of no association between NPC risk and the use of aspirin to treat ear, nose, and throat disease . Another study reported that a diet with greater inflammatory potential may play a role in increasing NPC risk .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Because of the overall lack of association with NPC risk, our findings suggest that anti‐inflammatory treatment with herbal tea is unlikely to play a causal role in NPC prevention. This result is consistent with our prior finding of no association between NPC risk and the use of aspirin to treat ear, nose, and throat disease . Another study reported that a diet with greater inflammatory potential may play a role in increasing NPC risk .…”
Section: Discussionsupporting
confidence: 92%
“…Unlike herbal tea, the herbal plants used in soups, which are often mixed with meat, are simmered slowly for an extended time to improve positive energy rather than to treat symptoms of internal heat. Our results showing an inverse association with herbal soup intake are consistent with those from a hospital‐based case‐control study in Guangdong that found a significant decrease in NPC risk among persons who consumed herbal soup monthly (OR, 0.44; P < .03) or weekly (OR, 0.49; P < .001) …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, pathogenesis of NPC has not been fully understood. Etiology and pathogenesis studies suggest the causal factors of NPC may include Epstein‐Barr virus infection, genetic factors, chemical carcinogens, and disturbance in oncogenes and tumor suppressor genes . Due to the specific anatomical structure and position, NPC is preferentially treated by radiotherapy, which has greatly improved the remission rate of NPC treatment and raised the overall average of 5‐year survival rate to over 70% .…”
Section: Introductionmentioning
confidence: 99%
“…suppressor genes. [2][3][4][5] Due to the specific anatomical structure and position, NPC is preferentially treated by radiotherapy, 6,7 which has greatly improved the remission rate of NPC treatment and raised the overall average of 5-year survival rate to over 70%. 8 However, residues, local recurrence, and metastasis still impede the prognosis of NPC patients and limit further improvement in survival.…”
mentioning
confidence: 99%